LEGAL LINGUISTICS BEYOND BORDERS : language and law in a world of media, globalisation and social conflicts : relaunching the international language and law association (ILLA). - Vogel, Friedemann, 1983- (DUNCKER & HUMBLOT, 2019)
The world of law has changed in the last decades: it has become more globalized, multilingual and digital. The sections and contributions of this volume continue the interdisciplinary discussion about the challenges of this change for theory and practice of law and for the International Language and Law Association (ILLA) relaunched in 2017. First, the book gives a broad overview to the research field of legal linguistics, its history, research directions and open questions in different parts of the world (United States, Africa, Italy, Spain, Germany, Nordic countries and Russia). The second section consists of contributions about the relation of language, law and justice in a globalized world with a focus on multilingual and supranational law in the EU. The third section focuses on digitalization and mediatization of the law, the last section reports about the discussion at the ILLA relaunch conference in 2017.